Pemahaman Perspektif Keuangan Sebagai Salah Satu Indikator Kinerja Utama Usaha Mikro, Kecil, dan Menengah (UMKM) di Kecamatan Sidayu Gresik - Ismiyah, Elly; Widyaningrum, Dzakiyah; Nuruddin, Mochammad (Conscilience: Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
MSMEs as one of the pillars of the nation's economy are sometimes run by people who only have business capital. Limited knowledge and ability sometimes becomes a thing that results in not real benefits being gained but rather pseudo-profits. For some MSMEs, having their business running is a success in itself, being able to buy raw materials and pay for workers is sometimes a measure that the business is running smoothly. Indicators such as rate and period of return, break-even point, Net Present Value (NPV), and so on never occurred to them that they were indicators of the performance of a business. MSME actors who are members of ASUMSI in fact have various educational backgrounds, not all of them have the knowledge and ability to manage administration and finances, therefore it is felt necessary to provide an understanding regarding the financial perspective as one of the main performance indicators of MSMEs which is packaged in community service activities.